Association of Serum Pepsinogens With Esophageal Squamous Cell Carcinoma Risk: A Systematic Review and Meta-Analysis - Yang, Zhen-Xiao; Yan, Lu-Bin; Xie, Peng; Hu, Peng; Zhao, Wenjing; Lu, Yi; Xing, Xiangbing; Liu, Xudong (Frontiers in Oncology, 2022)
Background Serum pepsinogens are serological biomarkers of gastric atrophy and the latter is a risk factor for esophageal squamous cell carcinoma (ESCC). However, the association of serum pepsinogens with ESCC risk remains unclear. This systematic review and meta-analysis aimed to assess the relationship between serum pepsinogen I (PGI) and pepsinogen I: pepsinogen II ratio (PGR) and ESCC risk. Methods PubMed, Embase, and Web of Science were searched for articles on the effect of serum PGI and PGR on ESCC risk, published up to the end of February 2022. Meta-analysis with a random-effect model was used to calculate pooled odds ratios (ORs) and 95% confidence intervals (CIs). Results Five case-control studies and three prospective studies were included. In comparison with the high categories, the low categories of serum PGI (OR: 1.92, 95%CI: 1.45-2.56) and PGR (OR: 1.70, 95%CI: 1.01-2.85) were associated with an increased risk of ESCC, though a substantial heterogeneity was observed in serum PGR (I2 = 60.2%, P = 0.028) rather than in serum PGI (I2 = 46.4%, P = 0.070). In stratified analysis by study quality, the significant risk effect on ESCC was remained for PGI (OR: 2.05, 95%CI: 1.48 - 2.84) and PGR (OR: 2.07, 95%CI: 1.17 - 3.75) when only the studies with high quality were pooled. Conclusions Based on the available studies, thought limited in number, this systematic review along with meta-analysis suggests that low serum PGI and low PGR may be related to an increased risk of ESCC. This present study provides evidence for using serum pepsinogen biomarkers in predicting ESCC. More delicate well-designed cohort studies with high study quality are needed and dose-response analysis should be performed.